The magician an adaptation from the Yiddish of I.L. Peretz - Shulevitz, Uri 1935-; Peretz, Isaac Leib 1851 or 2-1915. (New York London Macmillan Pub. Co. Collier Macmillan Publishers, 1985)
An old couple with neither food nor candles to celebrate Passover receive a mysterious visitor who supplies everything they need.
Originally published: New York : Macmillan, 1973.
Keywords: Passover -- Fiction